Components of the essential oil fraction of betel leaf (piper bettle linn) and the antibacterial activity test against several types of gram-positive bacteria - Febriyati (International Journal on ObGyn and Health Sciences, 2022)
The beetle, or Piper betle (Linn. ), is a member of the family Piperaceae and is commonly employed in beetle eating. Beetle leaves essential oils were distilled using steam and water and then separated into their component time periods. A total of 0.061%, 0.034%, 0.027%, and 0.015% were obtained from samples of F1, F2, F3, and F4 fractions, respectively. In a GC-MS analysis of essential oils, the five most abundant chemical components were identified as chavibetol, caryophyllene, patchouli alcohol, phenol,2-metoksi- 4(1-prophenyl)-acetate, and 4-allyl-1,2-diacetoxybenzene. This antibacterial action is thought to be due to the presence of all of these primary chemical components. Essential oils from beetle leaves were tested for their antibacterial properties using the microdilluton technique. All of the essential oil fractions were shown to be effective against Staphylococcus epidermidis and Streptococcus mutans but ineffective against Bacillus subtilis. All essential oil components have 0.25% MIC values against Staphylococcus epidermidis. But the most sensitive bacteria to the fourth component were Steptococcus mutans, at 0.25 percent. After treating bacteria with 1 MIC and 2 MIC of the oils, a vandalism test on the bacteria's cell walls revealed the oils' inhibitory action.